Highly Water-Dispersible Graphene Nanosheets From Electrochemical Exfoliation of Graphite - Park, Si-Woo; Jang, Byungkwon; Kim, Han; Lee, Jimin; Park, Ji Young; Kang, Sung-Oong; Choa, Yong-Ho (Frontiers in Chemistry, 2021)
The electrochemical exfoliation of graphite has been considered to be an effective approach for the mass-production of high-quality graphene due to its easy, simple, and eco-friendly synthetic features. However, water-dispersion of graphene produced in the electrochemical exfoliation method also has been a challenging issue because of the hydrophobic properties of resulting graphene. In this study, we report the electrochemical exfoliation method of water-dispersible graphene importantly containing the relatively low oxygen-content <10 % without any assistant dispersing agents. Through the mild in-situ sulfate-functionalization of graphite under control of alkaline electrochemical conditions using a pH buffer, the highly water-dispersible graphene could be produced without any additional separation processes of sedimentation and/or centrifugation. We found the resulting graphene sheets to be with the high crystalline basal planes, lateral sizes of several μm, and thickness <5 nm. Furthermore, the high aqueous dispersion stability of as-prepared graphene could be demonstrated using a multi-light scattering technique, showing very little change in the optical transmittance and the terbiscan stability index over time.